Being mindful at work: a moderated mediation model of the effects of challenge stressors on employee dedication and cynicism. Issue 6 (2nd November 2021) - Tong, Jiajin; Oh, Jo K.; Johnson, Russell E.
ABSTRACT: Researchers have found the effects of challenge stressors to be contradictory, sometimes showing positive effects and other times showing negative effects. To disclose the nature of this inconsistency, our study takes a resource-based behavioural approach to examine why and when challenge stressors are beneficial or harmful for employees. Specifically, we examine how trait mindfulness affects the pursuit of different coping behaviours (i.e., resource building versus resource draining) when faced with challenge stressors, which further translate into outcomes of employee dedication and cynicism, respectively. A sample of 163 employees from various organizations finished surveys on focal research variables in three waves. Using structural equation modelling, we confirmed the hypothesized model. Our findings provide behavioural mechanisms explaining the contradictory effects of challenge stressors and establish a cognitive basis for selecting adaptive coping behaviours. People were provided with knowledge on practical behavioural copings, and organizations and practitioners should recruit or cultivate individuals with high mindful awareness for high-demanding jobs to avoid ineffective copings and corresponding ill-being.